Serodiagnosis of bovine fasciolosis by enzyme linked immuno sorbent assay in Chennai, Tamil Nadu - LATCHUMIKANTHAN, A; SOUNDARARAJAN, C (The Indian Journal of Animal Sciences, 2013)
Excretory/ secretory (E/S) antigen of adult Fasciola gigantica worms was used for diagnosis of fasciolosis in cattle and buffaloes sera collected from different places in and around Chennai, Tamil Nadu using enzyme linked immuno sorbent assay (ELISA). Alcoholic fractionation (75%) and DEAE-sephadexA-25 anion exchange chromatography were used for the purification of E/S antigen. In this study, optimum dilution of E/S antigen, serum and conjugate were 1 in 100 (5 Î¼g/ml), 1 in 200 and 1 in 5000, respectively, were used as standardized by checker board titration. A total of 321 sera samples consisting of 168 cattle and 153 buffaloes were tested using ELISA and also dung samples examined by sedimentation method for comparing the sensitivity of both tests. Out of 321 animals examined 19 (5.91%) were positive for egg of Fasciola sp., 41 (12.77%) for amphistome egg, 38 (11.83%) for strongyle egg, 6 (1.86%) for Strongyloides sp. egg and 2 (0.62%) for mixed (both amphistome and strongyle eggs) infection in coprological examination. A total of 29 sera samples (17.26%) of cattle and 38 sera samples (24.83%) of buffaloes were found to be positive in ELISA test. Cattle sera samples showed 100% sensitivity and 95.09% specificity in ELISA. Similarly, sera samples from buffaloes also showed 100% sensitivity and 92.10% specificity in comparison to faecal examination method. ELISA was highly sensitive and specific in detecting higher percentage of positive animals than faecal examination and can be recommended for routine use in seroepidemiological surveys of Fasciola gigantica infection.